Wild Edible Plants: SDGs Strategy in the Kamajong Crater Forest Support Area - Sriwahjuningsih; Diah I. Putri (Journal of Tropical Ethnobiology, 2022)
Data collection on natural resources, especially wild edible plants (WEPs) in the forest around Kamojang Crater, needs to be done because it is a life support area for the Garut Regency and Bandung Regency. It has abundant biological wealth, community dependence on forest resources is high, and there is still a lack of data collection on the use of WEPs by the community to support sustainable development (SDGs). Environmental management and sustainable use of natural resources are problems that still need to be solved. The aims of this study were to (1) conduct a systematic study of WEPs used by communities in the forest buffer zone of Kamojang Crater, (2) record traditional knowledge related to WEPs, (3) analyze various uses of WEPs, and (4) evaluate species of significant cultural significance to communities in the Kamojang Crater forest buffer zone. The study carried out semi-structured interviews, key informant interviews, and participatory observations in the forest buffer area of Kamojang Crater, Samarang Subdistrict, Garut Regency, West Java, focusing on the nearest village to the Kamojang Crater. A total of 50 informants were involved in the snowball method to obtain information about WEPs, including local names, food categories, parts used, consumption methods, and other local uses. Several quantitative and qualitative methods have been conducted, consisting of RFC and CFSI calculations to identify the most culturally significant WEPs, and ANOVA to evaluate the variables of sex, age, occupation, and education. The study obtained data on 80 species from 37 families of WEPs consumed by the community in the forest buffer area of Kamojang Crater. The families are Asteraceae (19.23%), Euphorbiaceae (6.41%), Solanaceae (6.41%), Malvaceae (5.13%), and Apiaceae (5.13%). WEPs as side dishes with high CFSI values were Limnocharis flava (L) Buchenau, and Pilea melastomoides (Poir.) Bl., Nasturtium officinale W.T. Aiton, Oenanthe javanica (Blume) DC., Monochorea vaginalis (Burm. f.). Analysis of community age affects knowledge about WEPs, while gender, education, and occupation of the informants have not influenced it.